(untitled) (El-Wahat Journal for Research and Studies, 2021)
The Aimof Thisstudyis The Determination Of The Principles Determinants In The Long- And The Short Run Of Householdssaving In The Algerian Economy During The Period (1970-2014),In Order To Identify Appropriate Policies That Stimulate The Increase Of Household Savings. To Achieve The Objective Of The Study, The Autoregressive-Distribution (ARDL) Approach Was Adopted. The Results Showed The Existence Of Long-Term Relationship Between The Variables Of The Study. It Shows Up A Positive And Significant Effect Of Disposable Income And Financial Depth, On Households Saving, While There Was A Negative And Significant Effect For Both GDP And The Rate Of Age Dependency On Household Saving; In Contrast, There Was No Significant Effect For Each Of The Real Interest Rate And The Inflation Rate On The Household Saving In The Short And The Long Run.